2020
DOI: 10.1038/s43247-020-00052-z
|View full text |Cite
|
Sign up to set email alerts
|

Weak orogenic lithosphere guides the pattern of plume-triggered supercontinent break-up

Abstract: The importance of nonrigid geological features (such as orogens) inside tectonic plates on Earth’s dynamic evolution lacks thorough investigation. In particular, the influence of continent-spanning orogens on (super)continental break-up remains unclear. Here we reconstruct global orogens and model their controlling effects on Pangea break-up. We show that while loci of Pangea break-up are linked to mantle plumes, development of continental rifts is guided by orogens. Rifting at Central Atlantic is driven by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…It was found that plume erosion decreases lithospheric strength and controls the timing or even occurrence of continental break-up. Plumes can help to trigger final continental break-up by weakening lithosphere where it is already thinned, as hot plume material feeds into existing rifts and sutures, and plumeinduced melts can thin even thick cratonic lithosphere and facilitate rifting 292,293 .…”
Section: Breaking Up Continents and Initiating Subductionmentioning
confidence: 99%
“…It was found that plume erosion decreases lithospheric strength and controls the timing or even occurrence of continental break-up. Plumes can help to trigger final continental break-up by weakening lithosphere where it is already thinned, as hot plume material feeds into existing rifts and sutures, and plumeinduced melts can thin even thick cratonic lithosphere and facilitate rifting 292,293 .…”
Section: Breaking Up Continents and Initiating Subductionmentioning
confidence: 99%
“…Such weak zones, or damage zones, significantly differ from the surrounding lithosphere, for example, compositionally or mechanically, for example, due to failed rifts. Weak zones thus represent rheological “memory” which can be recalled, for example, for subduction initiation (e.g., Crameri et al., 2020; Gurnis et al., 2000) or supercontinental breakup (e.g., Dang et al., 2020). Given that continental plates record geology for ∼10 times longer than the more rapidly recycled oceanic lithosphere, memory effects may thus be most important for continents.…”
Section: Introductionmentioning
confidence: 99%
“…past subduction zones, orogens, shear zones), the physico-chemical interaction between upwellings and lithospheric architecture, and the large-scale stress field. Pre-existing zones of weakness play a critical role in combination with mantle upwellings during continental breakup 39 and studies of interactions between asthenospheric flow and craton geometry suggest that sharp craton margins, such as that imaged around the CASZ, are more resistant to deformation and erosion than gradual margins (e.g. Rehoboth Block) 40 .…”
Section: Implications For the Evolution Of Cratonic Lithospherementioning
confidence: 99%